FUSULINIDS AND PERMIAN SCALE OF THE TETHYS - Leven E.Ja. (My University, 2004)
The curve depicting generic diversity of Permian fusulinids has two distinct peaks: the Asselian-Sakmarian and Midian. The in-between minimum corresponds to the end of the Bolorian Age. The most significant extinctions of fusulinids are recorded in the terminal Midian (71% of all genera), Bolorian (48%), Asselian (27%), and Sakmarian (23%) ages. A renewal of prime importance took place in the Kubergandian Age, when 52% of new genera appeared in fusulinid community. These data suggest that history of Permian fusulinids can be divided in two principal (Asselian-Bolorian and Kubergandian-Dorashamian) and four second-order periods of evolution (Asselian-Sakmarian, Yakhtashian-Bolorian, Kubergandian-Midian, and Dzhulfian-Dorashamian). Two main periods of evolution corresponding to the Lower and Upper Permian of traditional East European scale are suggested to be termed as the Cisuralian and Tethysian subsystems. The subsystems are divisible into the Uralian, Darvasian, Yangsingian, and Lopingian series corresponding to second-order periods of fusulinid evolution. The suggested scheme is consistent with traditional two-part subdivision of the Permian System. In distinction from the three-series global chronostratigraphic scale accepted recently, series in the suggested scheme are more proportional and better corresponding to the natural stages in evolution of marine biota. The global scale with its strict criteria used to define boundaries between series and stages is hardly applicable in the Tethyan region. This is evident from diverse opinions concerning position of the Guadalupian Series lower boundary in Tethyan sections.
Keywords: Permian; Paleozoic::Permian; Палеозой::Пермская